Parenting patterns in children's freedom to marry at a young age (case study of Tapian Nauli 1 Village Community, Central Tapanuli Regency) - Br Marbun, Siti Anggreni; Ismail, Ismail (Trigin Publisher, 2024)
Parenting patterns applied by parents to children are the most important part that needs to be considered because they form a mindset and influence children's actions in doing something. In the current rampant early marriage/young marriage, it is also inseparable from one form of parenting pattern. This study aims to examine in more depth the form of parenting patterns of parents today, as well as the impacts caused by the occurrence of acts of child freedom to marry at a young age in the community of Tapian Nauli 1 Village, Central Tapanuli Regency. This type of research is descriptive-qualitative which uses survey and interview methods with parents and children who have early marriage/young marriage aged 16-21 years in Tapian Nauli 1 Village, Central Tapanuli Regency. The results of the study showed that the parenting pattern applied by parents in Tapian Nauli 1 Village, Central Tapanuli Regency is a Democratic parenting pattern. Parenting patterns with an average of using permissive and democratic parenting patterns, where parents give their children trust in doing something as long as they are considered capable of being responsible for their choices, one of which is getting married at a young age. The results of this study are expected to provide insight for parents and policy makers regarding the importance of the role of education and healthy parenting in preventing early marriage.